The Implementation of Task-Based Learning to Improve Students’ Ability in Reading Comprehension of Historical Events Through Recount Text - Lestari, Tarisa Ayu; Gaffar, Muhammad Andriana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Learning English as a second language requires reading skills. The ability to read helps students gain information, expand their vocabulary, and solve problems better. However, many students need help understanding reading, especially in a second language. As a result, effective approaches are needed to improve students’ reading comprehension. This study uses task-based learning methods (TBL) to improve students’ understanding of reading historical events through text recount. This research is carried out using qualitative methods and class action research. Checklists of observations, field records, and interviews are the tools used. At SMK Terpadu Ad-Dimyati Bandung, 25 class ten students were involved in this study. Research results show that using TBL to learn to read and understand historical events through text recount has a positive effect. Students better understand reading and are more actively involved in learning activities. Students can use TBL to discover social functions, text structure, and language elements in recount text. In addition, they acquire new vocabulary and improve their ability to understand reading. According to this study, TBL may improve students’ reading comprehension in a second language. To help students understand difficult reading, teachers should use these learning strategies. Using texts that narrate historical events can also help students learn more about history and improve their reading skills.